Mormons as Citizens of a Communist State: A Documentary History of the Church of Jesus Christ of Latter-day Saints in East Germany, 1945–1990 - Rajtar, Małgorzata (A journal of church and state, 2012)
Mormons as Citizens of a Communist State is an interesting, informative, and well-written volume by a member of the Church of Jesus Christ of Latter-day Saints (the LDS Church; the Mormons), who served in the North German Mission from 1958 to 1960 and later in the Freiberg Temple, “the only temple of the Church built behind the Iron Curtain” (p. 261), opened in June 1985. The book was originally published in German in 2008 under the title Mormonen und Staatsbürger: Eine dokumentierte Geschichte der Kirche Jesu Christi der Heiligen der Letzten Tage in der DDR.